Perbandingan Sistem Kesehatan di Negara Berkembang dan Negara Maju - Ririn Noviyanti Putri (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
The health system is a term that includes personal, institutions, financing, information, commodities and Government governance strategy in providing prevention and treatment services to the community. The health system was created with the aim of can respond to the needs and expectations of the community-owned healthcare in fulfillment of a fair and equitable. Then, good healthcare in developing countries as well as developed countries do need a reform, reorientation, and revitalization. This study aimed to know the comparison of health systems in developed and developing countries. Analysis study of the writing is done through literature review. Developing countries and developed countries experienced many challenges in building a strong health system and reliable. Health systems in developed countries look better compared to developing countries, it can be seen from the public health status and health problems. Health systems in each country vary greatly, but one has the same objective namely to enhance public health degrees extended. Every developed country or developing country has pros and cons of each of any health system that has been applied. The success of a health system of a country depends on the spirit, dedication, perseverance, hard work, good teamwork, ability (Human Resources, facilities), the sincerity of the organizers, as well as the participation of the community in order to achieve Universal Health Coverage in increasing degrees of better public health.